Flock of shoes - Tsiang, Sarah; Leng, Qin (Toronto Annick Press, 2010)
Abby loves her pink and brown sandals with the lime green trim. She wears them everywhere until one day while swinging high, the sandals flip off Abby's feet and fly away with the birds migrating south for the winter. All winter long even though Abby grows to love her warm and comfy boots, she wonders what her sandals might be up to, and where her boots will go when the weather grpws warmer.
97452
Keywords: Sandals -- Juvenile literature; Boots -- Juvenile literature; Seasons -- Juvenile literature